MORAXELLA SPECIES DIVERSITY IN INFECTIOUS BOVINE KERATOCONJUNCTIVITIS IN NOTHERN KAZAKHSTAN - Kuibagarov , M.A.; Kamalova , D.K.; Shustov , A.V.; Suminov , A.A.; Karibaev , T.B.; Ryskeldina , A.Zh.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2018)
The purpose of this work was to study bacterial species diversity in Moraxella involved in infectious bovine keratoconjunctivitis (IBK) in Northern Kazakhstan. DNA were isolated and Moraxella spp. cytotoxin A fragments were amplified in 29 samples taken from cattle with clinical signs of IBK. Nucleotide sequence analyses and phylogenetic studies showed that Moraxella bovis DNA was present in ten samples, Moraxella bovoculi/Moraxella ovis DNA was present in eight samples, and that mixed profiles (mixed-infection or contamination) were found in eleven samples. Moraxella bovoculi/Moraxella ovis were isolated from bovine biological material with clinical signs of IBK for the first time in Kazakhstan.